Literature Review: Technology Development and Utilization of Augmented Reality (AR) in Science Learning - Rahmatullah Rahmatullah; Desi Ramadhanti; Rika Nuryani Suwarno; Heru Kuswanto (Indonesian Journal of Applied Science and Technology, 2021)
Problems in learning science become important notes for teachers because there are still many students who are constrained in understanding the material. Constructive science material is a challenge for teachers to present good learning. One solution that can be used to build or understand the concept of science is with the help of technology. The technology that is starting to develop in the world of education today is augmented reality (AR). The purpose of the literature review is to review the use and utilization of AR technology on the success of learning in the classroom. The literature review method is based on the analytical method by processing the information contained in the literature. The data collected is in the form of qualitative data which is then described in the form of an in-depth explanation. The results of the analysis show that the form of AR development in the world of education uses more marker-based tracking models. The test results of several studies show that the use of AR technology has a positive effect on learning success. However, the effect of AR has so far only been tested on students' learning attitudes and low-level abilities. There is still little testing on the high-level abilities of students.